2023
DOI: 10.3389/fpls.2023.1237295
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormonal modulation of the drought stress in soybean: outlook, research progress, and cross-talk

Shifa Shaffique,
Saddam Hussain,
Sang-Mo Kang
et al.

Abstract: Phytohormones play vital roles in stress modulation and enhancing the growth of plants. They interact with one another to produce programmed signaling responses by regulating gene expression. Environmental stress, including drought stress, hampers food and energy security. Drought is abiotic stress that negatively affects the productivity of the crops. Abscisic acid (ABA) acts as a prime controller during an acute transient response that leads to stomatal closure. Under long-term stress conditions, ABA interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…Due to its rich nutritional content, foods processed from soybeans have become one of the most favored sources of sustenance [ 64 ]. Despite the annual increase in soybean production, environmental stress remains a significant factor affecting soybean yield [ 6 ]. Among various environmental stresses, drought is one of the most impactful abiotic stressors on soybean quality [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its rich nutritional content, foods processed from soybeans have become one of the most favored sources of sustenance [ 64 ]. Despite the annual increase in soybean production, environmental stress remains a significant factor affecting soybean yield [ 6 ]. Among various environmental stresses, drought is one of the most impactful abiotic stressors on soybean quality [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that drought stress reduces soybean germination rates and net photosynthetic rates, leading to significant decreases in biomass accumulation, pod set rates, and per plant grain yield [ 65 , 66 ]. Given its importance as a staple food crop, research on soybean drought resistance has garnered extensive attention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation